Parental influences on adolescent sexual decision making - Andres, Shandi D. (Kansas State University, 2010)
This M.S. report provides an evaluative review of research on parental influences on adolescent sexual decision-making. Data show that a significant proportion of never-married female and male teens (ages 15-19) have had sexual intercourse at least once. Adolescent decisions on sexuality and possible consequences such as pregnancy or sexually-transmitted diseases may have profound personal and social impacts. Theoretical and empirical domains of parental influence are reviewed, including communication, morality, family structure and context, parental control, as well as the role of media. This review shows that adolescent sexuality has changed over time due to socio-historical factors and that parents continue to have an influence on their children’s decision-making abilities. Implications for applied professionals and researchers are discussed.
Keywords: adolescent; sexual; parental influence; decision making; Health Sciences, Human Development (0758); Psychology, Developmental (0620); Sociology, Individual and Family Studies (0628)